Mechanical, wear and fatigue behavior of silane‐treated corncob biosilica toughened epoxy resin composite reinforced with prickly pear short fibers. Issue 10 (28th May 2022) - Sathish Kumar, S.; Manimaran, R.; Anbukarasi, K.
Abstract: This research focused on investigating the mechanical, wear, and fatigue behavior of an epoxy composite toughened with corncob biosilica (CCB) and prickly pear fiber (PPF). The primary aim of this research was to improve the load bearing effect of high‐brittle matrix by adding eco‐friendly fiber and particle. The surface treatment on the fiber and particle was done using an amino silane, 3‐Aminopropyltrimethoxysilane (APTMS). The natural fiber composites are prepared by hand layup process and characterized in accordance with ASTM standards. The experimental results indicated that the addition of fiber and particles increased the tensile and flexural strength up to 61% and 50%, respectively. Similarly, it is noted that the biosilica particles improved the bonding and reduced the rate of wear of composites, as well as lowered the stress intensity factor. A lowest wear rate of 0.037 and COF of 0.38 were noted for EFC2 composite designation. The morphological study of the fractured composites revealed improved fiber adhesion to the matrix. This reduced intensity of stress, increased wear resistance and higher fatigue life ensures the composite's application in structural and industrial applications. Abstract :